Soil sample timing, nitrogen fertilization, and incubation length influence anaerobic potentially mineralizable nitrogen. Issue 2 (15th April 2020) - Clark, Jason D.; Veum, Kristen S.; Fernández, Fabián G.; Kitchen, Newell R.; Camberato, James J.; Carter, Paul R.; Ferguson, Richard B.; Franzen, David W.; Kaiser, Daniel E.; Laboski, Carrie A. M.; Nafziger, Emerson D.; Rosen, Carl J.; et al.
Abstract: Understanding the variables that affect the anaerobic potentially mineralizable N (PMNan ) test should lead to a standard procedure of sample collection and incubation length, improving PMNan as a tool in corn ( Zea mays L.) N management. We evaluated the effect of soil sample timing (preplant and V5 corn development stage [V5]), N fertilization (0 and 180 kg ha −1 ) and incubation length (7, 14, and 28 d) on PMNan (0–30 cm) across a range of soil properties and weather conditions. Soil sample timing, N fertilization, and incubation length affected PMNan differently based on soil and weather conditions. Preplant vs. V5 PMNan tended to be greater at sites that received < 183 mm of precipitation or < 359 growing degree‐days (GDD) between preplant and V5, or had soil C/N ratios > 9.7:1; otherwise, V5 PMNan tended to be greater than preplant PMNan . The PMNan tended to be greater in unfertilized vs. fertilized soil in sites with clay content > 9.5%, total C < 24.2 g kg −1, soil organic matter (SOM) < 3.9 g kg −1, or C to N ratios < 11.0:1; otherwise, PMNan tended to be greater in fertilized vs. unfertilized soil. Longer incubation lengths increased PMNan at all sites regardless of sampling methods. Since PMNan is sensitive to many factors (sample timing, N fertilization, incubation length, soil properties, and weather conditions), it is important to follow a consistent protocol to compare PMNan among sites and potentially use PMNan to improve corn N management.